One pot microwave-assisted synthesis of Ag decorated yolk@shell structured TiO2 microspheres1. Issue 15 (25th February 2015) - Yang, Yong; Wang, Guozhong; Gu, Gang; Li, Qian; Kang, Shenghong; Zhang, Yunxia; Ng, Dickon H. L.; Zhao, Huijun
<x xml:space="preserve">Abstract</x> A facile and extremely fast one-pot microwave-assisted synthesis of Ag decorated yolk@shell structured TiO2 microspheres was reported.